Sistem Informasi Stok Barang Menggunakan QR-Code Berbasis Android - Syam, Muhammad Luthfi; Erdisna (Jurnal Informatika Ekonomi Bisnis, 2022)
Inventory of goods is a number of finished goods, raw materials, materials in process owned by a trading company for the purpose of selling or further processing. Inventory must be well controlled so that the availability of goods is always met. This activity is very supportive in improving service to buyers. This study aims to control the supply of goods that can always be done by mobile. The system used is based on Android with QR-Code support. The system used is an Android cellphone, so that data and information in the warehouse can be accessed and controlled anywhere and anytime. The data processed is computer equipment at the Ardha Computer Store in Padang. The results of this system can control inventory very well, so that controlling goods becomes easier and faster. So that this system can be used and is very supportive in controlling the stock of goods.